Effects of manganese complexes of curcumin and diacetylcurcumin on kainic acid-induced neurotoxic responses in the rat hippocampus - Yaowared Sumanont (2018)
This study aimed to investigate the mechanism underlying the protective effects of manganese complexes of curcumin (Cp-Mn) and diacetylcurcumin (DiAc-Cp-Mn) on kainic acid (KA)-induced excitotoxicity in the rat hippocampus. Systemic injection of KA (10 mg/kg, i.p.) caused seizures and increased the expression of neurotoxic markers, immediate early genes [c-jun, cyclooxygenase 2 (COX-2), brain-derived neurotrophic factor (BDNF), and heat shock protein 70 (hsp70)] and a delayed response gene [inducible nitric oxide synthase (iNOS)], which were measured at 6 and 72 h after KA injection, respectively, in the hippocampus. Pretreatment with Cp-Mn (50 mg/kg, i.p.) and DiAc-Cp-Mn (50 mg/kg, i.p.) but not with curcumin (50 mg/kg, i.p.) delayed the onset of KA-induced seizure without affecting the seizure score. KA injection induced c-Fos immunoreactivity in DG, CA1, and CA3 hippocampal regions, the expression of which peaked at 6 h after injection. Cp-Mn and DiAc-Cp-Mn treatment significantly decreased c-Fos expression elicited by KA. Moreover, Cp-Mn and DiAc-Cp-Mn administration suppressed the KA-induced expression of c-jun, COX-2, BDNF, and iNOS mRNA, whereas curcumin attenuated only iNOS mRNA expression. No compounds tested had an effect on KA-induced hsp70 expression. It is therefore likely that in addition to radical scavenging and SOD-like activities, the suppression of potential neuronal injury marker expression by Cp-Mn and DiAc-Cp-Mn, contributes to the neuroprotective activities of these compounds, which are superior to those of curcumin, on KA-induced excitotoxicity in the hippocampus. These results suggest the beneficial effects of Cp-Mn, and DiAc-Cp-Mn on the treatment of excitotoxicity-induced neurodegenerative diseases. © 2007 Pharmaceutical Society of Japan.